The Social Programs and Services among Senior Citizens in Datu Saudi Ampatuan - Nezzar Fahima Unsi Ali; Marsharita Guiamalon Kasim (RIRAI Publisher, 2022)
The study aimed to find out the Programs and Services offered among Senior Citizens in Selected Barangay of Datu Saudi Ampatuan Municipality. The study focused on demographic profile of the respondents in terms of age, gender, educational attainment and monthly income, the programs and services offered in the municipality. The description method was used in this study. This study was conducted particularly in Datu Saudi Ampatuan Municipality. In three barangays, the barangay Madia, barangay Dapiawan and barangay Elian in Datu Saudi Ampatuan Maguindanao. Datu Saudi Ampatuan, is a 4th class municipality in the province of Maguindanao, according to the 2020 census, it has a population of 12,890 people.The respondents were male and female between 60-70 years old Senior Citizens from three barangays representing the barangay of Madia, Barangay Dapiawan Barangay Elian in Datu Saudi Ampatuan Maguindanao. Barangay Madia is the highest registered Senior Citizens they have 98 registered senior citizens. Weighted mean was used to analyze the data gathered on the extent of the program and services for all senior citizens. The findings of the study revealed that Majority of respondents age 60-64 years old (4.33%). Majority of the respondents were female (56.67%). Majority of respondents were elementary (46.67%). The respondents were less extensive were doing the programs and services with the mean of 2.64. The common problems encountered by the respondents was no Companion with frequency of (16), followed by physical Appearance (14), and updated medical prescriptions (13). Most of the respondents recommend that there must be provide lifetime identification card (with validation) it gained a frequency of 26, followed by abolish membership fee afrequency of (19), and Home visit of OSCA representative (9).